INFORMATIVE BOOK ILLUSTRATION DESIGN RELATED TO THE USE OF SOCIAL MEDIA AS EDUCATION FOR CHILDREN - Ramadhini, Sabhina Rizka; Apsari, Diani; Lawe, I Gusti Agung Rangga (eProceedings of Art & Design, 2024)
This design aims to create an illustrated book that highlights the use of Social Media, as well as educating children on understanding Social Media. This understanding of Social Media needs to be done in order to empower young readers with the knowledge and critical thinking skills necessary to engage with social media safely and responsibly. With the use of social media among children, the development influenced by social media will also shape the child's character and personality. The tendency of young children to be captivated by digital media is quite powerful, causing them to focus on the rapidly changing features of digital media, including videos, sounds, and other interactive features. The final results of this design have shown that illustrated books can be the answer to the problems of using Social Media. By fostering a balanced and informed approach to social media use, this educational tool encourages children to learn what's wrong and what's right. Younger generation with the digital literacy skills needed to thrive in a technology-driven world while safeguarding their well-being in the online realm. Keywords: social media, book illustration, educative, children